Disparities in smoking during pregnancy by sexual orientation and race-ethnicity - Caroline Sten Hartnett; Zackery Butler; Bethany G. Everett (Elsevier, 2021)
The intersection between sexual orientation and race-ethnicity is emerging as an important dynamic for health. Prior research indicates that sexual orientation can have very different health implications for White, Black, and Latina individuals and that these patterns are unpredictable. Here we use U.S. data from the National Survey of Family Growth (2006-2019, n = 15,163 pregnancies) to examine how an important health indicator - smoking during pregnancy - is shaped jointly by sexual orientation and race-ethnicity. Smoking during pregnancy was more common among sexual minority women (both bisexual-identified and heterosexual-identified who expressed same-gender attraction/behavior), compared to heterosexual women. Second, the association between sexual orientation and smoking during pregnancy differed by race-ethnicity: sexual minority status was more strongly associated with smoking among Latina women, compared to White women. Finally, the subgroup with the highest rates of smoking during pregnancy was bisexual White women. These findings indicate that smoking rates among pregnant sexual minority women warrant attention (regardless of race-ethnicity), particularly as births within this group are rising. It is important to address structural factors that may create more stress for sexual minority women, since smoking is often a response to stress. These findings also highlight the role of heterogeneity: low smoking rates among pregnant Latina women mask within-group disparities.